Systematic Review of Low‐Density Lipoprotein Cholesterol Apheresis for the Treatment of Familial Hypercholesterolemia. Issue 7 (July 2016) - Wang, Anthony; Richhariya, Akshara; Gandra, Shravanthi R.; Calimlim, Brian; Kim, Lisa; Quek, Ruben G. W.; Nordyke, Robert J.; Toth, Peter P.
Abstract : Background: Apheresis is an important treatment for reducing low‐density lipoprotein cholesterol (LDL‐C) in patients with familial hypercholesterolemia (FH). We systematically reviewed the current literature surrounding LDL‐C apheresis for FH. Methods and Results: Electronic databases were searched for publications of LDL‐C apheresis in patients with FH. Inclusion criteria include articles in English published in 2000–2013 that provide descriptions of practice patterns, efficacy/effectiveness, and costs related to LDL‐C apheresis in patients with FH. Data were stratified by country and FH genotype where possible. Thirty‐eight studies met the inclusion criteria: 8 open‐label clinical trials, 11 observational studies, 17 reviews/guidelines, and 2 health technology assessments. The prevalence of FH was not well characterized by country, and underdiagnosis was a barrier to FH treatment. Treatment guidelines varied by country, with some guidelines recommending LDL‐C apheresis as first‐line treatment in patients with homozygous FH and after drug therapy failure in patients with heterozygous FH. Additionally, guidelines typically recommended weekly or biweekly LDL‐C apheresis treatments conducted at apheresis centers that may last 2 to >3 hours per session. Studies reported a range for mean LDL‐C reduction after apheresis: 57–75% for patients with homozygous FH and 58–63% for patients with heterozygous FH. Calculated annual costs (in US$2015) may reach US$66 374 to US$228 956 per patient for weekly treatment. Conclusions: LDL‐C apheresis treatment may be necessary for patients with FH when drug therapy is inadequate in reducing LDL‐C to target levels. While apheresis reduces LDL‐C, high per‐session costs and the frequency of guideline‐recommended treatment result in substantial annual costs, which are barriers to the optimal treatment of FH.